Chemogenetic dissection of a prefrontal-hypothalamic circuit for socially subjective reward valuation in macaques - Atsushi Noritake; Taihei Ninomiya; Kenta Kobayashi; Masaki Isoda (Nature Communications, 2023)
Abstract The value of one’s own reward is affected by the reward of others, serving as a source for envy. However, it is not known which neural circuits mediate such socially subjective value modulation. Here, we chemogenetically dissected the circuit from the medial prefrontal cortex (MPFC) to the lateral hypothalamus (LH) while male macaques were presented with visual stimuli that concurrently signaled the prospects of one’s own and others’ rewards. We found that functional disconnection between the MPFC and LH rendered animals significantly less susceptible to others’ but not one’s own reward prospects. In parallel with this behavioral change, inter-areal coordination, as indexed by coherence and Granger causality, decreased primarily in the delta and theta bands. These findings demonstrate that the MPFC-to-LH circuit plays a crucial role in carrying information about upcoming other-rewards for subjective reward valuation in social contexts.